2020
DOI: 10.1088/1757-899x/712/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Resilient Modulus of Porous Asphalt Incorporating Steel Fiber

Abstract: Porous Asphalt (PA) is known as a highly permeable asphalt surface that design to be permeable pavements for stormwater control and reduce the stormwater runoff. However, the structure is subjected to damage from cracking, rutting, stripping, and rapid aging under the effects of repeated vehicle loading, hot climates, and heavy rainfall. To overcome this, PA needs to modify using high tensile strength like steel fiber. Thus, this study aims to evaluate the performance of PA with the addition of steel fiber and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
4
2
0
Order By: Relevance
“…The results of this test for the analyzed mixtures are shown in Figure 8. As can be observed, the values of the resilient modulus ranged from 1187 to 3599 MPa, values in accordance to those found in previous research [57,65,66] for PA mixes using PMBBs.…”
Section: Resilient Modulussupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this test for the analyzed mixtures are shown in Figure 8. As can be observed, the values of the resilient modulus ranged from 1187 to 3599 MPa, values in accordance to those found in previous research [57,65,66] for PA mixes using PMBBs.…”
Section: Resilient Modulussupporting
confidence: 91%
“…The results of this test for the analyzed mixtures are shown in Figure 8. As can be observed, the values of the resilient modulus ranged from 1187 to 3599 MPa, values in accordance to those found in previous research [57,65,66] for PA mixes using PMBBs. Analyzing the influence of the filler material, it can be observed that CA provides higher average values of the resilient modulus than CS does for all dosages, indicating that CA produces a higher energy dissipation in the elastic range than mixtures with CS.…”
Section: Resilient Modulussupporting
confidence: 91%
“…After reaching its optimum content, the resilient modulus value of the sample shows a decreasing value. This trend is consistent with a study by [14] and [29] in which with the modification of the asphalt binder improves the resilient modulus value significantly [30]. For the resilient modulus value of the nano titanium modified sample, the pulse repetition periods used are 1000, 2000 and 3000 ms respectively.…”
Section: Resilient Modulussupporting
confidence: 90%
“…After adding the ZJ-I regenerating agent, the area of the individual bee-like structure of the regenerated asphalt gradually decreases, and the number of bee-like structures increases, which makes the large molecular weight content decrease, thus alleviating the aging degree 5. After adding the ZJ-I rejuvenator, the free energy of the asphalt surface and adhesion work increased, thus enhancing the adhesion of asphalt and aggregate, and finally, the best dosing of the ZJ-I rejuvenator was determined to be 7% (Shao-peng et al, 2002;Radzi et al, 2020;Sharma et al, 2020;Elio et al, 2021;Yin and Pan, 2022;Han et al, 2022)…”
Section: Discussionmentioning
confidence: 99%
“…However, DOP plasticizers can adversely affect the hightemperature shear and aging resistance of asphalt, so some materials that can improve the high temperature and aging resistance of asphalt need to be added. Nie et al (2019) and Radzi et al (2020) and Sharma et al (2020) and Shao-peng et al (2002)) found that adding hydrogenated C9 petroleum resin to plasticizers can better improve the aging resistance of asphalt. determined the microscopic morphology and the results proved that the addition of petroleum resin could indeed alleviate the aging of SBS-modified asphalt.…”
Section: Introductionmentioning
confidence: 99%